Multiphysics modeling framework for composite structural batteries with modified carbon fibers as electrodes. (October 2021) - Hong, Zhiguo; Hu, Zihan; Yang, Ruiheng; You, Junjie; Fu, Yu; Zhou, Limin; Yin, Sha
Abstract: The interfacial strength and electrochemical performance of composite structural battery can be simultaneously enhanced by employing modified carbon fibers (MCFs) as electrode. In this study, an electrochemical-mechanical coupled modeling framework is developed to clarify the multiphysics nature of composite structural battery and guide their further optimal design. Effects of the thickness ratio of cathode to anode, electrode thickness and the volume ratio of modified layer on CFs for the electrochemical and mechanical properties are investigated. An optimal thickness ratio of MCFs cathode to anode exists for better electrochemical performance, while thinner MCFs electrode will trigger greater specific capacity. In addition, the volume fraction of carbon fiber in composites and that of modified layer on CF respectively dominate longitudinal modulus and electrochemical capacity. Highlights: Laminated composite structural battery with modified carbon fibers is proposed. An electrochemical-mechanical coupled modeling framework is developed. Effects of critical parameters are investigated to guide optimal battery design.